Synthesis and antibacterial activity of difluoromethyl cinnamoyl amides - Martinez, Mario David (2020)
Series of novel amides of isoferulic acid, where the phenolic hydroxyl was replaced by a difluoromethyl group, were synthesized and their in vitro antibacterial activities assayed against fourteen bacterial strains (six Gram-positive and eight Gram-negative). A one-pot methodology was developed to obtain the 30-(difluoromethyl)-40-methoxycinnamoyl amides using Deoxofluor® as a fluorinating agent. The N-isopropyl, N-isopentyl, and N-(2-phenylethyl) amides 11b, 11d and 11g were the most active and selective against Mycobacterium smegmatis (MIC = 8 µg/mL) with 11b and 11g displaying negligible or no cytotoxicity against HepG2 and A549 cells. Thirteen analogs of N-isopropylamide 11b were also synthesized and their antibacterial activity assayed. Results show that the difluoromethyl moiety enhanced antibacterial activity and selectivity towards M. smegmatis, changing the microorganism inhibition profile of the parent compound. The selectivity exhibited by some of the compounds towards M. smegmatis makes them potential leads in the search for new narrow spectrum antibiotics against M. tuberculosis.